Scala 1:1. La ratio ontopoietica dell’Isomorfismo - Cavedagna, Veronica; Poccia, Daniele (Philosophy Kitchen - Rivista di filosofia contemporanea, 2017)
Following the mathematical use of isomorphism, which is a one-to-one correspondence between at least two structures or forms, the article extends and reconsiders the meaning of this notion in respect to three fundamental philosophical problems: the origin of meaning, the role of images in the formation of knowledge and the morphogenesis of the real. We argue that isomorphism could be understood as a heterotopian scale in which the overlapping of the maps with the territory it represents, results in a harmonic proliferation of realities which directly map onto the concepts they embody. As such, in order to describe it, we equal isomorphism to an ontopoietical method that allows for the transition from an analogical (and humanistic) metaphysics, to a pluralistic (and impersonal) ontology.